Honorable Bandit - Bouldrey, Brian (University of Wisconsin Press, 2024)
Brian Bouldrey traveled to the island of Corsica, with its wine-dark Mediterranean waters, powdered-sugar beach sand, sumptuous cuisine, and fine wine. And then he walked away from all of them. Bouldrey strapped on a backpack and walked across Napoleon's native land with the same spirit many choose to dance or drink: to celebrate, to mourn, to think, to avoid thinking, to recall, to ignore, to escape, and to arrive. This wonderfully textured account of a two-week ramble along a famous Corsican hiking trail with his German friend Petra (she was good at the downhills while he was better at the uphills) offers readers a journal that is a launching point for reflection: thoughts on cultural differences, friendship, physical challenge, personal challenge, and getting very, very lost. Part travelogue, part memoir, and part lampoon, this book offers readers an impressionistic view of a little talked about yet stunningly beautiful landscape. Best Books for General Audiences, selected by the American Association of School Librarians and the Public Library Association Runner-up, Best Travel Book, National Association of Travel Journalists